Nature's fury [ - Bernanke, Jamie; Fiocca, Richard; Johnston, Jud; Rosenfeld, Michael (The National Geographic Explorer collection, 1994)
Earthquakes,hurricans, tornadoes, floods: these colossal powers of nature have had dramatic consequences for humankind. But as massive as these forces are, the stories of heroism and tragedy are very personal. You'll meet heroes, fighting to save homes and lives, but see victims, too, suffering unspeakable tragedies. Join scientists as they study the elemental killers